Examination of Sexual Violence in Islamic Boarding Schools in Lombok: An Islamic Legal Perspective and Formulation of Preventive Strategies - M. Ali Fikri; Fahrurrozi Fahrurrozi (Madania: Jurnal Kajian Keislaman, 2024)
This study aims to explore the problem of sexual violence in Islamic boarding schools in Lombok, by examining the perspective of Islamic law and formulating prevention strategies. Sexual violence in religious educational environments such as Islamic boarding schools is often invisible and overlooked, even though it has serious impacts on victims and the reputation of the institution. Using a qualitative approach, this study collected data through interviews with Islamic boarding school administrators, teachers, and other relevant parties, and examined applicable policies and practices. This study evaluates how Islamic legal principles, including protection of individual honor and rights, can form the basis for formulating prevention strategies. From an Islamic legal perspective, sexual violence is considered a serious violation of the principles of justice, honor, and protection of human rights. The Quran and hadith teach that forced sexual intercourse without consent is a major sin, which can be punished both in this worldly and the hereafter, in accordance with the principles of qisas and ta'zir. The research findings indicate the importance of counselling and training for Islamic boarding school administrators, as well as the need to strengthen internal regulations and cooperation with the authorities. This research is expected to contribute to formulating concrete steps that are effective in preventing sexual violence in Islamic boarding schools, while maintaining the integrity of Islamic-based education. Penelitian ini bertujuan untuk menelusuri permasalahan kekerasan seksual di pesantren di Lombok, dengan mengkaji perspektif hukum Islam dan merumuskan strategi pencegahannya. Kekerasan seksual di lingkungan pendidikan agama seperti pesantren seringkali tidak terlihat dan terabaikan, meskipun memiliki dampak serius terhadap korban dan reputasi institusi. Dengan pendekatan kualitatif, penelitian ini mengumpulkan data melalui wawancara dengan pengasuh pesantren, guru, serta pihak terkait lainnya, dan meneliti kebijakan serta praktik yang berlaku. Kajian ini mengevaluasi bagaimana prinsip-prinsip hukum Islam, termasuk perlindungan terhadap kehormatan dan hak individu, dapat menjadi landasan dalam menyusun strategi pencegahan. Dalam perspektif hukum Islam, kekerasan seksual dianggap sebagai pelanggaran serius terhadap prinsip-prinsip keadilan, kehormatan, dan perlindungan hak asasi manusia. Al-Qur'an dan hadis mengajarkan bahwa tindakan pemaksaan hubungan seksual tanpa persetujuan adalah dosa besar, yang dapat dikenakan hukuman baik secara duniawi maupun ukhrawi, sesuai dengan prinsip qisas dan ta'zir. Temuan penelitian menunjukkan pentingnya penyuluhan dan pelatihan bagi pengelola pesantren, serta perlunya penguatan regulasi internal dan kerja sama dengan pihak berwenang. Penelitian ini diharapkan dapat memberikan kontribusi dalam merumuskan langkah-langkah konkret yang efektif dalam mencegah kekerasan seksual di pesantren, sekaligus menjaga integritas pendidikan berbasis Islam.